One Step Isolation of Bovine Asialoglycoprotein Receptor and Its Characterization by Sequence Analysis and MALDI Mass Spectrometry. Issue 2 (April 1999) - Seimetz, Diane; Frei, Eva; Schnölzer, Martina; Kempf, Tore; Wiessler, Manfred
Abstract : The asialoglycoprotein receptor (ASGP-R), which is responsible for the uptake of partially deglycosylated serum glycoproteins was isolated from bovine liver. The receptor was purified in one step from solubilized plasma membranes by affinity chromatography on 6-(β-D-lactosyl)-n-hexylamine coupled to N-hydroxysuccinimide activated Sepharose with a coupling degree of 7.6 μmol/ml gel. The preparation yielded two distinct polypeptides with apparent molecular weights of 48 and 43 kDa as determined by sodium dodecyl sulfatepolyacrylamide gel electrophoresis. A polyclonal antibody raised against the human ASGP-R recognized the bovine 43 kDa protein in Western blot analysis. The 48 and 43 kDa polypeptides were digested by trypsin and the digests were subsequently analyzed by matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry. Sequence analysis of four tryptic fragments, two each of the 48 kDa and of the 43 kDa polypeptides revealed that these were highly homologous to ASGP-R subunits from man, mouse and rat.